2017
DOI: 10.3233/cbm-170124
|View full text |Cite
|
Sign up to set email alerts
|

Low serum miR-98 as an unfavorable prognostic biomarker in patients with non-small cell lung cancer

Abstract: Therefore, serum miR-98 might be useful as a promising biomarker for prognosis prediction of NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Increasingly, studies are indicting that miRNAs may be key regulators in the initiation and progression of human cancers (15)(16)(17). For NSCLC, various miRNAs has been demonstrated to be aberrantly expressed, including miR-98 (18), miR-373 (19), miR-484 (20) and miR-1258 (21). The dysregulation of miRNAs may have tumor-suppressing or oncogenic roles in NSCLC, and thus serve crucial roles in the genesis and development of NSCLC by regulating multiple cellular biological processes (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, studies are indicting that miRNAs may be key regulators in the initiation and progression of human cancers (15)(16)(17). For NSCLC, various miRNAs has been demonstrated to be aberrantly expressed, including miR-98 (18), miR-373 (19), miR-484 (20) and miR-1258 (21). The dysregulation of miRNAs may have tumor-suppressing or oncogenic roles in NSCLC, and thus serve crucial roles in the genesis and development of NSCLC by regulating multiple cellular biological processes (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small noncoding RNAs that play a negative role in regulating gene expression [6,12]. MicroRNA expression is often increased in human malignant tumors, resulting in increased tumor growth, invasion, and metastasis [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Wang and his colleagues identified that 11 miRNAs, as well as their target genes and transcription factors, may be profitable in the prognostic prediction of NSCLC as biomarkers. In NSCLC blood samples, Wang et al [46] found that serum miR-98 expression was down-regulated in patients with NSCLC, and the decreased serum miR-98 was positively correlated with a worse TNM stage, lymph node metastasis, as well as unfavorable overall survival. Guo et al [47] showed that a decreased miR-204 level in plasma is associated with a poor prognosis in NSCLC patients.…”
Section: The Prognostic Value Of Mirnas In Nsclcmentioning
confidence: 99%
“…In NSCLC tissues, Li et al [49] report that miR-146 is highly expressed in cancer tissues, which can be used to predicts the prognosis of NSCLC. Wang et al [46] reveal that there is an obviously down-regulated miR-148b expression in NSCLC tissues, and the low miR-148b expression is closely related with poor survival of NSCLC patients. Zhang et al [50] demonstrate that a high expression level of miR-221 is associated with the short overall survival time for NSCLC patients.…”
Section: The Prognostic Value Of Mirnas In Nsclcmentioning
confidence: 99%